Applications of Equation of Continuity: Solving Real Life Problems using the Equation of Continuity (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Equation of continuity is interesting equation arising in fluid mechanics. The equation beingcomputationally attractive and is highly beneficial. In this paper we will solve real life problem with help ofequation of continuity. This equation also finds its applications in flows where compressibility is notsignificant.